Enabling national improvement in quality of care for renal colic. (12th December 2022) - Finch, William; Calvert, Robert C.; Fowler, Sarah; Hermans, Louisa; Dickinson, Andrew; Smith, Daron
Abstract : Objectives: To report the results of a clinical audit conducted by the British Association of Urological Surgeons (BAUS) of ureteric stone care pathways, with results reported with reference to national quality standards. Patients and Methods: The BAUS conducted a clinical audit of all patients presenting as an emergency to 107 hospitals in England during November 2020 with ureteric stones. All patients were followed up until 31 March 2021 and the inpatient and outpatient management received was recorded. Results: Data for 2192 patients across 117 units were submitted. The median (interquartile range [IQR]) number of patients per unit was 16 (9–27); 70% of patients were male and the median (IQR) patient age was 46 (34–59) years. Initial management was conservative treatment for 70% of patients. Overall, primary shockwave lithotripsy was performed in 34% of patients and primary ureteroscopy in 23% of cases when surgical intervention was required to treat the stone. However, 40% of patients in whom active intervention was appropriate underwent placement of a temporizing ureteric stent rather than undergo definitive surgical intervention at the outset. Female patients were less likely to have a computed tomography (CT) scan of the kidneys, ureters and bladder performed within 24 h of presentation (13% vs 7.3% for men [chi‐squared P = 0.01]) and to be given correct analgesia (66% vs 73% for men [chi‐squared P = 0.03]). Patients aged 60 years or older were also significantly less likely to be offered nonsteroidal anti‐inflammatory drug analgesia appropriately. In total, 87% of patients had their calcium measured within the last 2 years and 73% of patients had evidence of being offered stone prevention diet and fluid advice. Conclusions: The audit demonstrates that the National Institute of Health and Care Excellence Quality Standards are both measurable and achievable. However, there was considerable variation in the delivery of these standards, including with regard to sex and age, highlighting inequalities for patient care across the UK.